Preparação de eletrodos modificados com filmes poliméricos derivados de 4-metóxi-fenetilamina com incorporação de cristalitos de níquel para aplicação em reações de evolução de hidrogênio - Braghiroli, Rodrigo (2005)
Polymers containing non-extended systems have been known for more than 100 years, however, until about half of the 70s these systems were not of scientific interest due to the inferior quality when compared to conventional polymers. However, from the second half of the 70s, it was found that these films had the ability to conduct electrons when doped, similarly to metals, despite their organic characteristic. What was previously known as a large family of “worthless” macromolecular compounds has become extremely interesting for research from the applicable point of view. Currently, a large number of different monomers are starting materials for producing conductive polymers, using chemical or electrochemical methods, which may have special characteristics, such as ion exchanger when protonated, as well as its ability to perform covalent bonding. Its applications occur in several areas of science, such as, for example, energy storage, chemical sensors, biosensors and electroanalytics and electrocatalysis. Thus, in this work, the production of an electrochemically polymeric film deposited on glassy carbon was carried out, through cyclic voltammetry in acidic solution, using 4-methoxy-phenethylamine as a working monomer. The limit anodyne potential was studied, as well as the number of potential scans necessary for the formation of the film, and the tests were tested in solution containing the redox pair Fe2 + / Fe3T and by scanning electron microscopy (SEM). Subsequently, hexafluoroniquelate ions were incorporated by ion exchange, followed by reduction to generate nickel crystallites incorporated into the film. The efficiency of the incorporations was tested in hydrogen evolution reactions. It was concluded that the formation of polymeric films with derivatives of 4-methoxy-phenethylamine in different anodic potentials is possible, with the formed films having a passive character and the passivation is directly proportional to the number of potential scans performed, as well as to the increase of the limit anodic potential, which is insoluble in all known commercial solvents, except acetonitrile. It was possible to incorporate nickel crystallites in the formed films, observing that the saturation of the film occurs after the third incorporation of hexafluoroniquelate ions and the generation of hydrogen in the modified electrodes was greater when using modified electrode with polymeric film produced at greater potentials anodic, as well as a greater number of potential scans.